Economic valuation of anthropogenic-pressures effects on the Mendocinian piedmont. An application to discrete choice experiments - Farreras, Verónica (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
In general, the socioeconomic analysis of natural systems does not enter into the realms of natural science. This paper, however, estimates the human-welfare effects of possible anthropogenic-pressures on the Mendocinian piedmont by a lower provision of environmental services. The discrete choice experiment is applied to elicit the trade-offs in perceived values for three environmental services generated in the basins west of Gran Mendoza (alluvional risk, plant cover, and recreation) and for the costs of programmes designed to mitigate the intensity of such effects. Increased alluvional risk is the anthropogenic-pressure effect on the Mendocinian piedmont that most concerns the population, followed by a decrease of plant cover and recreation. An increase of 1% in alluvional risk is estimated to cost each person, on average, 24.13 pesos (2013 value) yearly in lost welfare, a figure equivalent in social welfare to a decrease of 6% in plant cover. These trade-off values may help policy makers, land managers, and ecologists to consider social preferences in the design of their programmes and activities.